Developing a Multiplayer Online Learning Environment to Web Support with AJAX3D and Virtual Reality - Souza, Everton; Lamounier, Edgard; Cardoso, Alexandre (RENOTE, 2007)
This paper presents Ludos Top - an educational 3D game that use virtual reality techniques, which can support multi-student with a new design model of networking on the web. The project has actively involved end-users to focus on increase interactivity through the use of versatile system architecture.We present a quick prototyping of a multi-user virtual world through the employment of Ajax, X3D and Web Services provides an efficient, flexible and robust means for distributed application. Results show improved network capabilities, in terms of interactive, ease of use, enjoyability, playability and usability.